Intercessory Prayer : Modern Theology, Biblical Teaching and Philosophical Thought. - Clements-Jewery, Philip, 1945- (Ashgate Pub., 2007)
How is prayer possible? How does prayer work? Why is it necessary to ask for God's gifts? Intercessory Prayer attempts to provide answers to questions about the nature of intercessory prayer. Critically examining biblical teaching and modern theological and philosophical thinking, this book shows how intercessory prayer may be seen as one of the means by which God enlists the freely-given cooperation of human persons in the realisation of the divine purpose. Clements-Jewery adopts a process view of the universe to show how intercession both makes certain possibilities greater and strengthens t.